Instrumen kesediaan pembelajaran terarah kendiri - Khairul Azhar Mat Daud; Nik Zulkarnaen Khidzir; Hasyamuddin Othman (Universiti Malaysia Kelantan, 2015)
The instrument of Self-Directed Learning Readiness Scale (SDLRS) is an instrument developed to measure students’ readiness for self-directed learning. The SDLRS instrument was developed by adapting the original instrument which is established from Guglielminno (1977). The original SDLRS instrument from Guglielmino (1977) has been adapted in order to mismatch its application with the local culture from a variety of aspects influencing the Malaysian education system. The particular aspects that influence the Malaysian educational system is management, implementation, learning systems, infrastructure, student motivation, achievement and students socioeconomics. The development of SDLRS is through a proper process with five main phases namely; language expertise, pilot test, the analysis of reliability and finally, the development of an instrument format. Through the analysis, it is found that the value of these instruments has a very high reliability of Cronbach alpha, α = 0.9204. Self-directed learning readiness is formed by three constructs such as Self-Management (Cronbach alpha, α = 0.8780), determination to learn (Cronbach alpha, α = 0.8634), and self-control (Cronbach alpha, α = 0.8496).